Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1186/1743-0003-9-3
|View full text |Cite
|
Sign up to set email alerts
|

Subjects with hip osteoarthritis show distinctive patterns of trunk movements during gait-a body-fixed-sensor based analysis

Abstract: BackgroundCompensatory trunk movements during gait, such as a Duchenne limp, are observed frequently in subjects with osteoarthritis of the hip, yet angular trunk movements are seldom included in clinical gait assessments. Hence, the objective of this study was to quantify compensatory trunk movements during gait in subjects with hip osteoarthritis, outside a gait laboratory, using a body-fixed-sensor based gait analysis. Frontal plane angular movements of the pelvis and thorax and spatiotemporal parameters of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
48
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 37 publications
7
48
0
Order By: Relevance
“…30,31 The range of tilting movement of the trunk in the coronal plane during walking was increased before surgery (5.2°), although not significantly compared to the healthy group (3.7°), and it further increased after surgery (5.9°) and showed a significant difference from the healthy group. Reininga et al 43 obtained similar findings in a comparison of trunk movement during walking using a body sensor in patients with osteoarthritis of the hip and healthy subjects. Trunk sway during walking is caused by a compensatory action to reduce pain by increasing coverage of the femoral head and reducing weight bearing on the hip joint by tilting the trunk toward the affected side in the stance phase of the affected side.…”
supporting
confidence: 65%
“…30,31 The range of tilting movement of the trunk in the coronal plane during walking was increased before surgery (5.2°), although not significantly compared to the healthy group (3.7°), and it further increased after surgery (5.9°) and showed a significant difference from the healthy group. Reininga et al 43 obtained similar findings in a comparison of trunk movement during walking using a body sensor in patients with osteoarthritis of the hip and healthy subjects. Trunk sway during walking is caused by a compensatory action to reduce pain by increasing coverage of the femoral head and reducing weight bearing on the hip joint by tilting the trunk toward the affected side in the stance phase of the affected side.…”
supporting
confidence: 65%
“…In 1 study, 66 swing duration originally reported as percentage of gait cycle was calculated from given values of the contralateral single-limb support time in seconds. Stride length was calculated as a function of cadence and speed in the studies by Reininga et al 67 and Watanabe et al, 77,78 cadence was calculated as a function of speed and stride length in 3 studies, 2,45,61 and speed was calculated as a function of stride length and cadence in 1 study. 54 Where studies reported values for both limbs in individuals with hip OA and in controls, symmetry indices were calculated.…”
Section: Additional Analysismentioning
confidence: 99%
“…53 The pooled mean and standard deviation for spatial-temporal data across 2 groups of individuals with preoperative hip OA in 2 studies, 36,45 across test-retest of individuals with hip OA conditions in 2 studies, 32,76 and across 2 groups of individuals with hip OA in 1 study 67 were used in the meta-analysis. In the control groups, the within-study pooled mean and standard deviation for relevant gait measures across dominant and nondominant lower limbs were used in 8 studies.…”
Section: Additional Analysismentioning
confidence: 99%
“…In the patient group, the static margin of stability was largest at the affected side, which suggests that patients walked with more lateral trunk inclination toward unaffected than toward affected, as Thurston (1985) reported for patients with more serious pain. Note, however that Reininga et al (2012) observed more inclination toward affected; however, in that study inclination toward affected was used as a preselection criterion.…”
Section: Frontal Plane Stabilitymentioning
confidence: 94%
“…Still, these margins co-depend on amplitude and speed of frontal plane trunk movements. Some HOA patients walk with lateral trunk inclination toward the affected side (Reininga et al, 2012). However, patients with more severe pain tend to walk with lateral inclination toward their unaffected side (Thurston, 1985).…”
Section: Introductionmentioning
confidence: 98%